International positive production externalities under a transfer payment scheme – the case for cooperation Charalampos Savvidis - Savvidis, Charalampos (SPOUDAI Journal of Economics and Business, 2011)
In the present work we try to find out whether the existence of positive international externalities generates an incentive for cooperation between governments and if the adoption of a transfer payments scheme moderates that intensive. We adopt a simple economic model incorporating the international linkage of national economies. Utility proves always to be higher when countries cooperate than when they play Nash to each other. We then add a transfer payment scheme and prove it intensifies the intensive to cooperate, since a moral hazard problem arises on the top of the free riding problem. JEL Classification: H23; F35; F42